2007
DOI: 10.4321/s0365-66912007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia tópica más subconjuntival versus retrobulbar en la esclerectomía profunda no penetrante

Abstract: RESUMENObjetivo: Comparar la eficacia y seguridad de la anestesia tópica-subconjuntival con la retrobulbar en la escleroctomía profunda no penetrante suplementada con 5-FU. Método: Se realizó un estudio prospectivo y aleatorizado de 30 pacientes consecutivos a los que se les practicó anestesia tópica-subconjuntival (n=14) o retrobulbar (n=16). Se evaluaron las condiciones operatorias, el confort del paciente, el dolor postoperatorio, el dolor total y el resultado quirúrgico en cuanto a bajada de presión intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The available literature is mainly focused on comparing the efficiency and safety of different laser devices and the effectiveness of new laser technologies. 1,2,4,11 At the same time, most of the research in ophthalmic analgesia was focused on the efficacy and safety of different anesthetic procedures and drugs for surgical procedures, particularly cataract surgery, 12,13,14 glaucoma surgery 15,16 or during vitreoretinal treatments. 17,18 The present study offered insights into the analgesia techniques for PRP by comparing topical anesthesia with a combined approach using topical and subconjunctival anesthetic injection.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature is mainly focused on comparing the efficiency and safety of different laser devices and the effectiveness of new laser technologies. 1,2,4,11 At the same time, most of the research in ophthalmic analgesia was focused on the efficacy and safety of different anesthetic procedures and drugs for surgical procedures, particularly cataract surgery, 12,13,14 glaucoma surgery 15,16 or during vitreoretinal treatments. 17,18 The present study offered insights into the analgesia techniques for PRP by comparing topical anesthesia with a combined approach using topical and subconjunctival anesthetic injection.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found no difference in outcome, when comparing subconjunctival LA and Ga 54 55 and subconjunctival vs Topical, 58 or subconjuctival vs retrobulbar (non-penetrating surgery). 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’. 59 …”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 99%
“…Most reported IOP at 1 year. These prospective randomized trials have failed to show any difference in trabeculectomy success rate when comparing―subconjunctival vs retrobulbar (non-penetrating surgery), 56 subconjunctival vs topical, 58 or peribulbar vs topical (phacotrabeculectomy). 57 Current evidence indicates no major effect of anesthesia technique on the level of IOP after trabeculectomy.…”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 99%